Pengembangan Website Interaktif sebagai Media Pemasaran UMKM Batagor Keliling - Aizil Nasri; Tasya Desma Albarokah; Sularno Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The mobile Batagor MSME faces challenges in expanding its market reach and increasing sales through conventional marketing methods. This study aims to develop an interactive website as an effective digital marketing medium for the MSME. The website is designed with features such as a product catalog, online ordering system, and social media integration to enhance customer interaction and accessibility. The research employs a Research and Development (R&D) approach, including needs analysis, design, development, and functionality testing of the website. Testing results show a 150% increase in website visits and a 40% increase in online transactions within three months after launch. These findings demonstrate that an interactive website can be an effective solution to expand market reach and boost sales for the mobile Batagor MSME in the digital era.